Arbitration of Neighborhood Ties and Honor: Building and Property Disputes before the Six-Man Council of Prague, 1547-1611 - Palmitessa, James R. (The sixteenth century journal, 2003)
This article examines building and property disputes before the Six-Man Councils of the Old and New Cities of Prague from 1547 to 1611. On one level, the disputes provide rich descriptive information about Renaissance architectural innovations and everyday interaction in this bilingual and multiconfessional city that was undergoing a transformation into a Habsburg residence. On another level, the disputes manifest a distinct form of urban popular culture associated with the material culture of housing. The essential nature of the disputes was rooted not in functional housing problems, but in social tensions formed around the construction, alteration, and access to boundaries, social as well as physical. Similar to other public acts of affront, such as slander and insult, the building disputes served as a tool, whereby an attack on another person and his or her house through a building dispute was an attack on that person's status and honor in the neighborhood.